Inclusive double-Pomeron exchange at the Fermilab Tevatron p̄p collider - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2004)
The double-Pomeron exchange (DPE) process p̄ + p → p̄′ + X + Y is investigated, where Y is a proton. The ratio of the number of DPE events in the region to the total number of events in the sample was 0.194±0.001±0.012. It was found that the value was lower than the prediction based on Regge factorization by a factor of 1.9 ± 0.2. It was indicated that the formation of a second rapidity gap in a single diffractive (SD) event is relatively unsuppressed. It was observed that the results favor those in which the Regge based shapes of the SD and DPE distributions remain unchanged and only the overall normalization is suppressed.